Risk of early‐onset breast cancer among women exposed to thoracic computed tomography in pregnancy or early postpartum. (23rd March 2018) - Burton, K. R.; Park, A. L.; Fralick, M.; Ray, J. G.
Abstract : Essentials Tests for pulmonary embolism expose women to low‐dose radiation. 5859 pregnancies had a thoracic computed tomography (T‐CT) vs. 1.3 million who did not. The adjusted hazard ratio for breast cancer was 1.17 (95% confidence interval 0.80‐1.70). The long‐term risk of breast cancer among women who had a T‐CT remains unknown. Summary: Background: The risk of breast cancer may be higher with direct exposure to ionizing radiation from thoracic computed tomography (CT) during pregnancy or the postpartum. We evaluated the short‐term risk of maternal breast cancer after exposure to thoracic CT during these periods. Methods: We completed a retrospective population‐based cohort study of all deliveries between 1995 and 2014 using universal healthcare databases in the province of Ontario, Canada. The main exposure was thoracic CT in pregnancy or ≤ 42 days postpartum. The passive exposure was ventilation‐perfusion scintigraphy (VQ) scan in pregnancy or ≤ 42 days postpartum. Each was compared to pregnancies unexposed to thoracic CT or VQ scan. The primary study outcome was newly diagnosed breast cancer starting 366 days post‐index delivery date. Results: A total of 5859 pregnancies were exposed to thoracic CT, 4075 to VQ scan and 1 292 059 to neither. Starting from 1 year after the index delivery, the median duration of follow‐up was 5.9, 7.3 and 11.1 years, respectively. A total of 10 129 women were diagnosed with breast cancer, of whom 9039 (89.2%) were aged ≤ 50 years. There were 27 new cases of breast cancer (7.1 per 10 000 person‐years) following thoracic CT vs. 10 080 (7.0 per 10 000 person‐years) among the unexposed, an adjusted hazard ratio (HR) of 1.17 (95% confidence interval [CI], 0.80–1.70). Following VQ scan exposure, the incidence rate of breast cancer was 7.0 per 10 000 person‐years, an adjusted HR of 1.23 (95% CI 0.81–1.87), compared with the unexposed cohort. Conclusion: Exposure to thoracic CT during pregnancy or the postpartum was not associated with an increased short‐term risk of maternal breast cancer. The long‐term risk should be studied.